Pulmonary embolism in pregnancy and the postpartum period – a literature review - Mliczek, Aleksandra; Obersztyn, Julia; Szczecińska, Adrianna; Glanert, Wiktoria; Kulawinek, Hubert; Mrozek, Piotr; Bajer, Jakub Maksymilian; Kasparek, Krzysztof Maksym; Kasparek, Grzegorz; Czech, Marta (Quality in Sport, 2026)
Background: Pulmonary embolism (PE) is a leading cause of maternal morbidity and mortality worldwide. Pregnancy and the postpartum period increase the risk of venous thromboembolism due to hypercoagulability, venous stasis, and endothelial injury. Diagnosis remains challenging because symptoms often overlap with physiological changes in pregnancy, delaying recognition and increasing the risk of adverse outcomes. Aim: To review current evidence on the epidemiology, risk factors, pathophysiology, clinical presentation, diagnosis, and management of pulmonary embolism during pregnancy. Material and methods: A narrative literature review was conducted using publications from PubMed and Scopus, including original studies, systematic reviews, and meta-analyses on pulmonary embolism during pregnancy and the postpartum period. Results: Pulmonary embolism in pregnancy presents significant diagnostic challenges due to nonspecific symptoms and physiological changes affecting clinical assessment. Pregnancy-adapted diagnostic algorithms combining clinical pre-test probability with D-dimer testing may improve diagnostic accuracy while reducing unnecessary imaging. When imaging is required, computed tomography pulmonary angiography and ventilation–perfusion scanning provide high diagnostic performance with acceptable safety. Management is based on risk stratification. Low-molecular-weight heparin is the first-line treatment for hemodynamically stable patients, whereas reperfusion therapies are reserved for high-risk cases. Conclusions: Pulmonary embolism remains a serious pregnancy complication requiring early diagnosis and prompt treatment. Advances in diagnostic strategies and management have improved patient care; however, further studies are needed to optimize risk assessment and treatment in this population.